Deconstructing Patterns of Stigma toward People Living with Mental Illness. (1st October 2018) - Ho, Andy H Y; Fong, Ted C T; Potash, Jordan S; Ho, Vania F L; Chen, Eric Y H; Ho, Rainbow T H
Abstract: The adverse effects of stigma on people living with mental illness (PLMI) have been well documented. This study aimed to investigate the latent structure of that stigma. The study respondents included 218 Chinese university students in Hong Kong who completed the Attribution Questionnaire. The latent structure of stigma was examined by factor mixture analysis and psychological correlates. The results supported the two-class, one-factor mixture model under a t distribution. Most of the sample ( n = 175; 80.2%) belonged to the low-stigmatizing class, with low to moderate expressions of stigma toward PLMI. Compared with the low-stigmatizing class, the high-stigmatizing class was significantly more likely to be male, not working, and younger and to report significantly higher social distance, personal distress, and empathetic concern. The different group profiles demonstrated a nuanced view of stigma toward PLMI. An appreciation of stigma's complexity could inform the development of more appropriately tailored psychiatric services and education and advocacy initiatives that foster greater mental health inclusion.